IMPLEMENTASI ACTIVE LISTENING DALAM MEMBANGUN KOMUNIKASI EFEKTIF ANTARA GURU DAN ANAK USIA DINI DI TK IDHATA I - Gizki Maharani; Bunga Rosani; Nurul Wahyuni; Armila Aulia; A. Nidha Eka Restuti Munawir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore the implementation of active listening in fostering effective communication between teachers and young children at IDHATA I Kindergarten. It also identifies the supporting and inhibiting factors affecting its implementation and examines its impact on the quality of communication throughout the learning process. A qualitative descriptive approach with a case study design was employed in this research.The research subjects consisted of school principals, class teachers, and group B children at IDHATA I Kindergarten. Data were collected through observation and interview techniques, then analyzed using Miles and Huberman's interactive analysis techniques which included data reduction, data presentation, and conclusion drawn. The results of the study show that the application of active listening by teachers is able to increase children's confidence in communication, strengthen the emotional relationship between teachers and children, and create a conducive and fun learning environment. In addition, teachers who practice active listening are better able to understand children's needs, emotions, and challenges, making the learning process more meaningful. However, its implementation continues to face several challenges, including limited time, differences in children's communication abilities, insufficient professional training, and teachers' administrative workload. Therefore, support from schools is essential through continuous training and professional development to help teachers implement active listening consistently and foster effective communication with young children.